(untitled) (Revista de Ciências Agroveterinárias, 2019)
Understanding of trace elements distribution in different soil chemical fractions and of the total mobility and concentration is essential for the diagnosis of contamination and the definition of remediation strategies for contaminated sites. This study aims to evaluate Cd behavior in the soil chemical fractions and Cd total concentration extracted by aqua regia of a Fluventic Dystrudept. After the contamination with increasing doses applied and incubation of the metal in the soil, samples were analyzed following the protocol described by GOMES et al. (1997) for sequential fractionation, and the ISO 11047 (1998) (aqua regia) for total extraction. Cd determination was performed by atomic absorption spectrometry. The results were subjected to analysis of variance. Regression equations were adjusted between the variables analyzed and the Cd levels were applied to the soil. Subsequently, the proportions of the Cd allocated in each fraction and the total recovered Cd were calculated. The increase in Cd levels applied to the soil of the experiment increased total Cd concentration and the concentration in the chemical fractions in the following order of intensity: iron oxides < soluble < residual < organic matter < exchangeable. Proportionally, under low concentrations, the element has higher tendency to bind with organic matter, iron oxides and residual fraction than with soluble and exchangeable fractions combined. In high concentrations, a combination of soluble and exchangeable fractions, which are the most mobile fractions in the soil, is more representative than other fractions. The extraction of total Cd by the aqua regia method returned values above 77% of the applied doses in the soil, presenting high efficiency for concentrations up to 200 mg kg-1.